Analysis of Regional Financial Management Performance and Level of Regional Independence in the Era of Regional Autonomy: Case Study of Semarang City in 2009-2013 - Mubarokah; Agus Munandar (HM Publisher, 2022)
This study aimed to analyze the effect the financial ability of Semarang City in order to support the implementation of regional autonomy, base on Semarang Budget Realization Reported the period of 2009 -2013. A descriptive comparative analysis used to measure the performance of regional financial management and the independence level of Semarang, consist of Regional Financial Independence Ratio, Degree of Decentralization Ratio, Local Native Income (PAD), effectiveness Ratio, and the Harmony Expenditure Ratio. Based on the analysis that has been obtained, the following results: from the analysis of the ratio of the degree of decentralization can be explained that the average ratio of the degree of decentralization is 25,87% of which is in the internal level of level 25%-50%, means already have a good ability to finance region development. Average Regional Financial Capabilities (KKD) ratio is 37.79% which is in the interval 25 % -50 % means that central government intervention has begun to decrease, because the region is considered a little more able to implement region autonomy. From the analysis of PAD effectiveness is more than 100%, it can be concluded that the overall performance of local financial management and the degree of independence of Semarang area continued to improve. It can be seen from some of the financial performance ratio is the ratio of the area of financial independence, the ratio of degrees decentralization, effectiveness ratio and the ratio continues to increase harmony and good effect on the autonomy of the region